Revised estimates of leprosy disability weights for assessing the global burden of disease: A systematic review and individual patient data meta-analysis. - Shri Lak Nanjan Chandran; Anuj Tiwari; Anselmo Alves Lustosa; Betul Demir; Bob Bowers; Rachel Gimenes Rodrigues Albuquerque; Renata Bilion Ruiz Prado; Saba Lambert; Hiroyuki Watanabe; Juanita Haagsma; Jan Hendrik Richardus (Public Library of Science (PLoS), 2021)
Background Leprosy is a chronic bacterial infection caused by Mycobacterium leprae, which may lead to physical disability, stigma, and discrimination. The chronicity of the disease and disabilities are the prime contributors to the disease burden of leprosy. The current figures of the disease burden in the 2017 global burden of disease study, however, are considered to be under-estimated. In this study, we aimed to systematically review the literature and perform individual patient data meta-analysis to estimate new disability weights for leprosy, using Health-Related Quality of Life (HRQOL) data. Methodology/principal findings The search strategy included all major databases with no restriction on language, setting, study design, or year of publication. Studies on human populations that have been affected by leprosy and recorded the HRQOL with the Short form tool, were included. A consortium was formed with authors who could share the anonymous individual-level data of their study. Mean disability weight estimates, sorted by the grade of leprosy disability as defined by WHO, were estimated for individual participant data and pooled using multivariate random-effects meta-analysis. Eight out of 14 studies from the review were included in the meta-analysis due to the availability of individual-level data (667 individuals). The overall estimated disability weight for grade 2 disability was 0.26 (95%CI: 0.18-0.34). For grade 1 disability the estimated weight was 0.19 (95%CI: 0.13-0.26) and for grade 0 disability it was 0.13 (95%CI: 0.06-0.19). The revised disability weight for grade 2 leprosy disability is four times higher than the published GBD 2017 weights for leprosy and the grade 1 disability weight is nearly twenty times higher. Conclusions/significance The global burden of leprosy is grossly underestimated. Revision of the current disability weights and inclusion of disability caused in individuals with grade 0 leprosy disability will contribute towards a more precise estimation of the global burden of leprosy.